Environmental factors associated with talent identification of women’s youth national team soccer players in the United States - Matthew Andrew; Samuel Wood; José M. Oliva-Lozano; Mirelle Van Rijbroek; Rick Cost; Matthew J. Reeves (PLoS ONE, 2025)
Female soccer has seen an exponential growth in popularity leading to significant investment in talent identification and development processes. Soccer federations can only identify, develop, and select from a pool of players that are born within the country, thus environmental factors play an important role in the process. Despite the United States (US) being one of the most successful female soccer nations, little is known about environmental factors and their influence upon players’ talent pathways. This study sought to examine the key environmental factors associated with the identification and development of players for the Women’s Youth National Team (WYNT). Semi-structured interviews were undertaken with 23 experienced scouts (11.6 ± 8.8 yrs) that ranged from 32.0 to 61.8 minutes in length (46.1 ± 8.3 mins) to explore their perceptions of the female soccer landscape in the US and how different environmental factors can impact talent identification and development. Four higher order themes emerged: (1) no established playing style; (2) finding players for WYNT; (3) players access to talent opportunities; and (4) limited involvement of the Soccer Federation in youth development. This study is the first to examine these issues in female soccer and US contexts, and further examination of the association between environmental variables and talent identification and development are required to ensure evidence-based decision making that is both female- and country-specific.